2019
DOI: 10.1177/0003702819875132
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Vacuum Ultraviolet Absorption Spectra: Paraffin, Isoparaffin, Olefin, Naphthene, and Aromatic Hydrocarbon Class Compounds

Abstract: The advent of a new vacuum ultraviolet (VUV) spectroscopic absorption detector for gas chromatography has enabled applications in many areas. Theoretical simulations of VUV spectra using computational chemistry can aid the new technique in situations where experimental spectra are unavailable. In this study, VUV spectral simulations of paraffin, isoparaffin, olefin, naphthene, and aromatic (PIONA) compounds using time-dependent density functional theory (TDDFT) methods were investigated. Important factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The use of experimental absorption spectra, combined with spectral library matching, and computed absorption spectra provided good results (Figure 3), however they concluded that improvements in computational methods are needed in order to derive more experimental-like spectra. In the recent work, Mao et al [28] This article is protected by copyright. All rights reserved.…”
Section: Vacuum Ultraviolet Spectroscopymentioning
confidence: 99%
“…The use of experimental absorption spectra, combined with spectral library matching, and computed absorption spectra provided good results (Figure 3), however they concluded that improvements in computational methods are needed in order to derive more experimental-like spectra. In the recent work, Mao et al [28] This article is protected by copyright. All rights reserved.…”
Section: Vacuum Ultraviolet Spectroscopymentioning
confidence: 99%
“…10 Very recently, Mao et al also investigated the absorption edge of various alkanes using a new benchtop FUV spectroscopic detector for gas chromatography and assigned the absorption in this region to Rydberg transitions. 21,22 They also reported that carrying out calculations without diffuse basis functions resulted in spectra that did not reproduce the experimental results well. 22 Morisawa et al showed that the absorption band of n-alkanes can be assigned to the s-Rydberg 3p transition by comparison with the results of quantum chemistry calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, time-dependent density functional theory (TDDFT) has been used to compare calculated and experimental VUV spectra. 17,2729…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, time-dependent density functional theory (TDDFT) has been used to compare calculated and experimental VUV spectra. 17,[27][28][29] Previous analysis of nitrate ester explosives such as ethylene glycol dinitrate (EGDN), nitroglycerine (NG), and pentaerythritol tetranitrate (PETN) at temperatures exceeding 240 C revealed various decomposition products such as nitric oxide, water, carbon monoxide, oxygen, and formaldehyde. 26,30 These decomposition products were determined via the VUV spectral database.…”
Section: Introductionmentioning
confidence: 99%